Minahasa Identity: A Culinary Practice - Gabriele Weichart (Antropologi Indonesia, 2004)
The geographic area I will focus on is the Minahasa region in North Sulawesi. There, in the eighteenth century the eight 'tribes' inhabiting the area were united into a single 'ethnic group' known as 'Minahasa' until today. Not only the Dutch colonial government but also the Protestant church put great efforts into this unifying and homogenizing process that was supposed to create a common identity for all Minahasan people. The effectiveness of those efforts can hardly be denied. Nevertheless, internal differences have continued to exist and they are based not only on 'traditional' concepts that divided the 'original' Minahasan tribes but also on the local population's experiences with immigrants from other parts of Indonesia and overseas (e.g. the Philippines and China). Although this is not a recent phenomenon, political and socio-economic developments during the last few years have had further impacts on demographic conditions and relations between different ethnic and religious 'groups'. Thus, the Minahasa-like other 'ethnic groups' in Indonesia-are confronted with a double binding of supposed needs and requests for diversity under a unifying umbrella-on the regional as well as national level. The paper will address the 'problem' from the perspective of a rural community in the south-eastern part of the region. Hence, local concepts of identity, their constructions and markers in everyday life, as being manifested in food and clothing for instance, will be given special consideration. It will also be taken into account that the media (esp. television) plays an important role in the formation and representation of ethnic and religious identity. The paper aims at showing how 'unity' and 'diversity' in this context are produced and reproduced on the village level and its relation to the national discourse.